Pembaruan Hukum ISlam dari Qawl Qadim ke Qawl Jadid dalam Madhhab Shafi'i - Abdurrohman Kasdi (AL-TAHRIR, 2013)
Abstract: Based on the action of al-Shafi’i that the Fatwa differs by the change of the [geographical] location. It was [even] said that this new Madh’hab [and Methodology] even started taking form just before he left Iraq to Mecca, others said [that it started to take form] before leaving Mecca, but what is definite though is that he wrote it and set its foundations in Egypt. Thus it has nothing to do with it being in Egypt or in Iraq. The consequence of this concept is that certain rules of Islam, would not apply, due to the new environment they live in, and that we live in a new time and age. So rules regarding riba, marriage, social interaction, international law, ruling systems, would need to be updated, according to the said principle. The proponents of this understanding use the example of Imam Shafi’i to legitimise their viewpoint.